Prevalence of body dissatisfaction and its effects on health-related quality of life among primary school students in Guangzhou, China - Wei Liu; Rong Lin; Chongshan Guo; Lihua Xiong; Siyu Chen; Weijia Liu (BMC, 2019)
Abstract Background The relationship between body dissatisfaction (BD) and health-related quality of life (HRQoL) has been well documented in adolescents and adults but is less clear in children, particularly in China. The aims of this study were to describe body image perception and dissatisfaction and to examine their effects on HRQoL among primary school students in Guangzhou, China. Methods A total of 5734 children aged 8-12 years from 29 schools completed self-report questionnaires, which included the Paediatric Quality of Life Inventory 4.0 for measuring HRQoL and Ma figural stimuli for measuring BD. Based on their level of BD, the children were divided into three groups: no dissatisfaction, mild dissatisfaction and moderate or high dissatisfaction. Based on the children's perceptions of their own body image, the groups were also categorized into just right, too fat and too thin groups. Height and weight were objectively measured using standardized methods, and a BMI z-score was derived using the age- and sex-specific WHO references from 2007 for children aged 5-19 years. Weight status was classified as underweight, healthy weight, overweight or obese. Results A total of 78.10% of children aged 8-12 years in Guangzhou had different levels of BD; boys had slightly higher levels BD than girls (p < 0.01), and obese children demonstrated the highest degree of BD (p < 0.01). However, BD levels did not differ significantly according to age (p = 0.194). Gender differences in body image perceptions were only found in children with a healthy weight (p < 0.01), but age differences in body image perception were present in both children with a healthy weight (p < 0.05) and underweight children (p < 0.05). Of the children with a healthy weight who were dissatisfied with their body image, 65.54% of the boys wanted to be heavier, whereas 52.95% of the girls wanted to be thinner (p < 0.01), and older children were more inclined to perceive themselves as too fat (p < 0.01). After controlling for the influence of confounding factors, significant trends for lower HRQoL scores with increasing BD levels persisted in all domains (p < 0.01). Conclusions BD is as common in children as in adolescents and adults and might be independently associated with HRQoL impairment. The present findings suggest that the current epidemic of BD is a threat to the health of primary school children in China, and prevention programmes for this population should be implemented in the future.